Processo de revitalização da produção familiar de batata no território do Polo da Borborema-PB: estudo de caso - Mélo, Crisoleide Silva de (2015)
Research institutions and family agriculture in an integrated, collective and participative way foster a transition of conventional agriculture for agroecology in the Territory of Borborema/PB. The action starts from the need to revert to the serious socio-environmental crisis generated by the use of conventional practices based on the Green Revolution. The objective of this research was to characterize a family agroecosystem, inserted in the Territory of Borborema / PB, in transition process and involved with the cultivation of agroecological potato (solanum tuberosum L.). The research was done and applied based on a case study, directed to a qualitative, descriptive and exploratory approach. They were adopted by observational, interactive methods, as well as photographic and audiovisual records. The analyzed agroecosystem, called in this work as Crisântemo, meets the criteria required by Law 11.326, of July 24, 2006, so that the agricultural unit is considered as family production. Considering that it has: predominance of family labor, family income of agricultural activities generated in the agroecosystem; area of property less than four fiscal modules, and direction of the family agroecosystem. In the agroecosystem the following subsystems were identified: plant production (annual farm, backyards, forage and trees) and breeding of animals (cattle, pigs and birds). Each subsystem has particular ecological characteristics that act in a systemic and integrated way making the agroecosystem sustainable. The following species were identified in the annual rows: potato, sweet potato, sweet herb, cassava, beans, maize, fava, pumpkin), quintals (chives, coriander, cabbage, lettuce, tomato, chuchu, elephantgrass), and in the sub-system trees (gliricídia, neem, hazelnut, sabiá, leucena, algaroba, coconut, soursop, cashew, papaya and guava). Traditional and innovative agroecological practices have been identified, related to seed management, soil management, water management, and animal husbandry. Agroecological practices of soil management are related to the organic fertilization mediated by the biodigestor and the mackerel, application of MB-4 (Pó de Rocha), minimum soil work, crop rotation and crop consortium. The agroecological transition process adopted in the agroecosystem has provided an increasing level of sustainability, and there is a commitment of family farmers not only to their family unit but also to the environment and future generations. Keywords: Agroecology; Family Farming; Agroecosystems; Sustainability